Immunomodulatory Effects of Agarwood Leaf Extract on RAW264.7 Murine Macrophages - Pang, Kok-Lun; Chin, Kok-Yong; Nirwana, Soelaiman I. (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2023)
Background: The immunomodulatory effects of plants have been utilised to enhance the immunity of humans against infections. However, evidence of such effects of agarwood leaves is very limited despite the long tradition of consuming the leaves as tea. Objective: This study aimed to investigate the immuno-modulatory effects of agarwood leaf extract (ALE) derived from Aquilaria malaccensis using RAW264.7 murine macrophages. Methods: In this study, RAW264.7 macrophages were incubated with ALE alone for 26 hours or ALE for 2 hours, followed by bacterial lipopolysaccharide for 24 hours. The nitrite and cytokine production (tumour necrosis factor-alpha (TNFα), interleukin (IL)-1β, IL-6, and IL-10), inducible nitric oxide synthase (iNOS), and cyclooxygenase-2 (COX2) expression in the macrophages were assayed. Results: The study showed that ALE alone was immunostimulatory on the macrophages by increasing the nitrite, TNFα, and IL-6 production and COX2 expression (p<0.05 vs. untreated unstimulated cells). Pre-treatment of ALE suppressed nitrite level and iNOS expression but enhanced TNFα and IL-6 production and COX2 expression (p<0.05 vs. untreated lipopolysaccharides (LPS)-stimulated cells). ALE also increased IL-10 production regardless of LPS stimulation (p<0.05 vs. untreated cells). Conclusion: ALE was able to promote the immune response of macrophages by upregulating pro-inflammatory cytokine levels and COX2 expression. It also regulated the extent of the inflammation by reducing iNOS expression and increasing IL-10 levels. Thus, ALE may have a role in enhancing the innate immune system against infection; however, its validation from in vivo studies is still pending.
Keywords: inflammation